Digital Financial Literacy and Digital Payment Behavior Among Millennials and Generation Z - Nurul Hidayati Indra Ningsih; Baiq Reinelda Tri Yunarni; Erwin Asidah (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study aims to analyze the influence of digital financial literacy on the behavior of using digital payment methods among Millennials and Generation Z in Mataram City. The background of this research is based on the growing use of digital financial services in Indonesia and the importance of financial literacy in supporting sound financial decision-making. A quantitative approach was employed through a survey method involving 100 respondents consisting of Millennials and Gen Z, using simple linear regression analysis and independent t-tests. The results revealed that digital financial literacy has a significant effect on digital payment behavior. However, the study also found a gap between high literacy levels and suboptimal actual behavior. The implications of this study highlight the need for financial literacy education programs tailored to generational characteristics and local contexts to foster sustainable financial inclusion